Modern America Totalitarian Surveillance through the Speculative Fiction Context of Margaret Atwood’s The Handmaid’s Tale (1985) - Benlahbib, Houria; Naoumi, Mohamed (University ofAmmar Theledji -Laghouat, 2022)
In a rapidly changing world where political hegemony and economic ambition are most noticeable, “speculative fiction” seems to be the most workable approach to the future. The term speculative fiction allows writers to superbly present their vision of the future, thus escaping the scorching image of science fiction. It can see as a wake-up call designed to warn readers and force them to acknowledge the dangerous direction that society is taking. The authors use fiction, alternate worlds, history, mystery, and time travels in this case. The meticulous study of Atwood’s novel The Handmaid’s Tale (1985) from the point of view of speculative fiction presents itself as an example of such a reading of the future. The novel takes place in the fictional totalitarian society of Gilead, and the story discusses the hypothesis of the subversion of the current “democratic” community of the United States of America by a totalitarian regime. The new imagined reality presents a futuristic wasteland influenced by current ideologies. Atwood has created a dystopian environment to provide critical insights into the phenomenon of totalitarian surveillance and the escalating crisis of lack of privacy and loss of freedom. This dissertation aims to reintroduce the reading of The Handmaid’s Tale as a speculative fiction text that examines the totalitarian politics prevailing today to provide an exemplary view of the modern American policy of surveillance and information monopoly where humanity and democracy advance in reverse to the backward, and the intellectual freedom of individuals descends to the bottom in a supposedly democratic country. This thesis will undertake an analytical, critical, and historical approach to conducting this study. Finally, this dissertation concludes by finding that the crisis of freedom loss, either physical or intellectual, in the fictional or real-world results from living under a totalitarian regime